Buletin Peternakan : EFFECT OF NONI FRUIT (Morinda citrifolia) POWDER AS FEED ADDITIVE ON INTESTINAL MICROFLORA AND VILI CHARACTERISTICS OF HYBRID DUCK - David Kurniawan, Eko Widodo,Irfan H Djunaidi (Peternakan UGM, 2016)
Noni fruit is a medicanal plant with biological activity like antimicrobial and antioxidant that could potentially be used as a feed additive in poultry. This research investigated the effect of noni fruit powder as feed additive on intestinal microflora and villi characteristics of hybrid duck.